Red Queen Takes White Knight: The Commercialisation of Accounting Education in Australia - Ted Watts; Graham Bowrey; C. J. McNair-Connolly (Australasian Accounting, Business and Finance Journal, 2015)
This paper investigates the adaptive and maladaptive consequences of changes resulting from the commercialisation of Australian universities, specifically their accounting schools, and aims to identify the organisational changes triggered by competition that affect the growth of universities over time. The paper synthesises organisational learning theory, benchmarking theory, mimetic isomorphism and institutional theories, which are presented as "the Red Queen", itself an evolutionary theory; this synthesis provides the theoretical underpinning. The Red Queen theory posits that competition triggers organisational learning, which in turn intensifies competition in rivals that ultimately triggers an adaptive response. This self-reinforcing process produces results that may be adaptive or maladaptive. There is evidence to support that “running fast” in terms of Red Queen evolution theory has allowed some universities to place competitive pressure on rivals and achieve elite levels of publications, international accreditation and improved international rankings. This search for improvement, driven by commercialisation, provided ways to improve performance, thus improving the university’s competitive strength. There is also evidence to support the belief that “running slow” provides maladaptive consequences that could affect growth rates, quality and staff performance. The use of the Red Queen hypothesis provides an evolutionary approach to the study of strategy, strategic change and organisations. This provides an opportunity to examine competition in universities as a force that continually disturbs equilibrium.
Keywords: Accounting education; adaptive and maladaptive consequences; commercialisation; higher education; Red Queen theory; strategic management